Variation in the FABP4 gene affects carcass and growth traits in sheep. (November 2018) - Yan, Wei; Zhou, Huitong; Hu, Jiang; Luo, Yuzhu; Hickford, Jon G.H.
Abstract: Fatty acid-binding protein 4 (FABP4) participates in fatty-acid transportation and variation in the gene has been reported to affect fat deposition in mammals. To assess the effects of variation in FABP4 on carcass and growth traits in sheep, two regions of the gene were investigated in 749 New Zealand Romney lambs. Five variants ( A 1   −   E 1 ) were found in region-1 (exon 2 − intron 2) and three variants ( A 2   −   C 2 ) were found in region-2 (exon 3 − intron 3). A 1 was associated with a decrease in leg meat yield, loin meat yield and total meat yield, whereas A 2 was associated with a decrease in weaning-weight and pre-weaning growth-rate. Haplotype A 1 -A 2 was found to be associated with a decrease in birth-weight, pre-weaning growth-rate, hot carcass weight, loin meat yield, shoulder meat yield and total meat yield, while haplotype A 1 -B 2 was associated with increased fat depth at the 12th rib (V-GR). Taken together, this supports the contention that variation in FABP4 affects growth and meat production in sheep.